The mysterious benedict society and the prisoner's dilemma ebook - Stewart, Trenton Lee (The Mysterious Benedict Society, 2009)
Join the Mysterious Benedict Society as Reynie, Kate, Sticky, and Constance embark on a daring new adventure that threatens to force them apart from their families, friends, and even each other. When an unexplained blackout engulfs Stonetown, the foursome must unravel clues relating to a nefarious new plot, while their search for answers brings them closer to danger than ever before. Filled with page-turning action and mind-bending brain teasers, this wildly inventive journey is sure to delight.